2023
DOI: 10.20525/ijrbs.v12i5.2663
|View full text |Cite
|
Sign up to set email alerts
|

The impact of overconfidence and herding bias on stock investment decisions mediated by risk perception

Abstract: This study examines the impact of overconfidence bias, herding bias, and risk perception on stock investment decisions. This study uses explanatory research with a quantitative approach. The population in this study is the Generation Z Society, the generation born between 1997-2012 in Malang City who invests in the capital market. The sampling technique used in the study was purposive sampling. Data collection was used through surveys using questionnaires, and the use of Likert scales to test instruments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…When making financial decisions, many investors have a propensity to follow the herd or overconfidence biases. Herding behavior results from the influence of risk perception on stock returns, as suggested by Almansour et al (2023), and is supported by Wibowo et al (2023) who stated that herding bias develops because of how much risk investors perceive from stock returns. Moreover, Almansour et al (2023) state that investors with overconfidence tend to possess a positive view of risk and demonstrate a greater propensity to embrace a risky approach when making investment decisions.…”
Section: Risk Perception As the Mediatormentioning
confidence: 81%
See 2 more Smart Citations
“…When making financial decisions, many investors have a propensity to follow the herd or overconfidence biases. Herding behavior results from the influence of risk perception on stock returns, as suggested by Almansour et al (2023), and is supported by Wibowo et al (2023) who stated that herding bias develops because of how much risk investors perceive from stock returns. Moreover, Almansour et al (2023) state that investors with overconfidence tend to possess a positive view of risk and demonstrate a greater propensity to embrace a risky approach when making investment decisions.…”
Section: Risk Perception As the Mediatormentioning
confidence: 81%
“…Herding behavior refers to a behavior in which an investor imitates the actions of another investment driven by a variety of causes and specific situations (Wibowo et al, 2023). Many investors may exhibit a delayed response to new information instead of relying on the trading actions of those believed to possess a higher level of expertise.…”
Section: Construct Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fitri and Cahyaningdyah (20) explained that overconfidence significantly influences derivative investment in the international market. Wibowo et al indicated that herding and overconfidence biases in investors can impair the quality of stock trading and investment decisions (21) . Furthermore, herding bias and overconfidence bias might lower investors' risk perception.…”
Section: Introductionmentioning
confidence: 99%
“…Risk perception can mediate between herding and overconfidence biases in investment decisions. Thus, investors should minimize the formation of bias for investment decisions and should diversify investment portfolios to reduce the risk [32].…”
Section: Introductionmentioning
confidence: 99%